The Role of Job Satisfaction in Mediating the Effect of Competency and Perceived Organizational Support on Education Performance: An Evidence from the Muhammadiyah University of Jember, Indonesia - Septy Holisa Umamy (International Journal of Management, Entrepreneurship, Social Science and Humanities, 2021)
Education personnel in higher education have an important role to support performance, so it is necessary to know the factors that affect performance. Efforts to improve performance by understanding organizational behavior. Organizational behavior will affect work behavior, including competence, Perceived organizational support and job satisfaction. The population of this research is 120 educational staff. The sampling method of this research is saturated sample. Data analysis used the Partial Least Square (PLS) method with SmartPLS software. The results in this study are all accepted hypotheses, both direct and indirect effects. Competency variables have a direct effect on job performance and satisfaction, Perceived organizational support have a direct effect on job performance and satisfaction. Job satisfaction has a direct effect on performance, job satisfaction acts as a mediating variable on the influence of competence on performance and the influence of perceived organizational support on performance. Suggestions in this study to improve competence need to provide training and provide career development to education personnel.